Immune Cell Subsets Evaluation as a Predictive Tool for Hepatitis B Infection Outcome and Treatment Responsiveness - Kandilarova Snezhina M.; Georgieva Atanaska I.; Mihaylova Anastasiya P.; Baleva Marta P.; Atanasova Valentina K.; Petrova Diana V.; Popov Georgi T.; Naumova Elissaveta J. (Folia Medica, 2017)
Background: The patient’s immune response is one of the major factors influencing HBV eradication or chronification, and it is thought to be responsible for the treatment success.